Cellulase production from mixed rice biomass as substrate in solid state fermentation - Chee, Cheau Yee (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Nowadays cellulase from lignocellulosic materials is being used extensively in fuel production. Therefore it is very important to investigate any cost-effective bioprocess that can improve the cellulase production. To produce cellulase in large volume at affordable prices, a fungal solid-state fermentation (SSF) process that uses lignocellulosic by-product from rice milling industry, mixed rice biomass (combination of rice husk and rice straw in ratio of 1:3) was introduced due to environmental problems caused by disposal of lignocellulosic biomass from agricultural wastes. Cellulase production using Trichoderma longibrachiatum fungi strain was discussed in this research since it has ability of producing extracellular cellulase in high yield. Physical pretreatment of raw material was performed using grinder and siever before producing pretreated sample by chemical pretreatment that involved the use of 2% sodium hydroxide (NaOH). Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) revealed that there were significant ultrastructural and functional group changes of mixed rice biomass during alkaline pretreatment. The result indicated that alkaline pretreatment had enhanced the cellulase production by causing the degradation of ester and glycosidic side chains resulting in structural alteration of lignin, cellulose swelling, partial decrystallization of cellulose, and partial solvation of hemicellulose successfully. Parameters of SSF were optimized using Central Composite Design for Response Surface Methodology by setting initial moisture content of SSF at a range of 40% - 80% and incubation temperature from 25 C to 45 C. Thirteen runs of experiment were performed to study the effect of these parameters on cellulase production. Cellulase production was enhanced from 0.1451 FPU/ml to 0.2500 FPU/ml at 60% initial moisture content and 49.1 C incubation temperature.